Effects of sprint interval training with active recovery vs. endurance training on aerobic and anaerobic power, muscular strength, and sprint ability - Sökmen, B.; Witchey, R. L.; Adams, G. M.; Beam, W. C. (The Journal of Strength and Conditioning Research, 2018)
This study compared sprint interval training with active recovery (SITAR) to moderate-intensity endurance training (ET) in aerobic and anaerobic power, muscular strength, and sprint time results. Forty-two recreationally active adults were randomly assigned to a SITAR or ET group. Both groups trained 3× per week for 10 weeks at 75% of VO2max for 30 minutes weeks 1-4, with duration increasing to 35 minutes weeks 5-7 and 40 minutes weeks 8-10. While ET ran on a 400-m track without rest for the full training session, SITAR sprinted until the 200-m mark and recovered with fast walking or light jogging the second 200 m to the finish line in 3× original sprint time. Maximal oxygen consumption (VO2max), anaerobic treadmill run to exhaustion at 12.5 km/h at 20% incline, isokinetic leg extension and flexion strength at 60 and 300°/s, and 50 m sprint time were determined before and after training. Results showed a significant improvement (p = 0.05) in absolute and relative VO2max, anaerobic treadmill run, and sprint time in both groups. Only SITAR showed significant improvements in isokinetic leg extension and flexion at 300°/s and decreases in body mass (p = 0.05). SITAR also showed significantly greater improvement (p = 0.05) over ET in anaerobic treadmill run and 50 m sprint time. These data suggest that SITAR is a time-efficient strategy to induce rapid adaptations in VO2max comparable to ET with added improvements in anaerobic power, isokinetic strength, and sprint time not observed with ET.